Investigating the Effect of One Year of Learning to Play a Musical Instrument on Speech-in-Noise Perception and Phonological Short-Term Memory in 5-to-7-Year-Old Children - MacCutcheon, Douglas; Füllgrabe, Christian; Eccles, Renata; van der Linde, Jeannie; Panebianco, Clorinda; Ljung, Robert (Frontiers in Psychology, 2020)
The benefits in speech-in-noise perception, language and cognition brought about by extensive musical training in adults and children have been demonstrated in a number of cross-sectional studies. Therefore, this study aimed to investigate whether one year of school-delivered musical training, consisting of individual and group instrumental classes, was capable of producing advantages for speech-in-noise perception and phonological short-term memory in children tested in a simulated classroom environment. Forty-one children aged 5–7 years at the first measurement point participated in the study and either went to a music-focused or a sport-focused private school with an otherwise equivalent school curriculum. The children’s ability to detect number and color words in noise was measured under a number of conditions including different masker types (speech-shaped noise, single-talker background) and under varying spatial combinations of target and masker (spatially collocated, spatially separated). Additionally, a cognitive factor essential to speech perception, namely phonological short-term memory, was assessed. Findings were unable to confirm that musical training of the frequency and duration administered was associated with a musicians’ advantage for either speech in noise, under any of the masker or spatial conditions tested, or phonological short-term memory.